Does the dysregulation of matrix metalloproteinases contribute to recurrent implantation failure?. (3rd April 2018) - Benkhalifa, Mustapha; Zayani, Yosra; Bach, Véronique; Copin, Henri; Feki, Moncef; Benkhalifa, Moncef; Allal-Elasmi, Monia
ABSTRACT: Introduction : The progress in in vitro fertilization (IVF) techniques for infertility management has led to the investigation of embryo implantation site proteins such as Matrix metalloproteinases (MMPs), which may have a key role in embryo-endometrium crosstalk and in the molecular mechanisms of the embryo implantation. Areas covered : Numerous studies have generated much information concerning the relation between the different proteins at the site of implantation such as cytokines, growth factors, adhesion molecules and MMPs. However, the exact role of the MMPs in embryo implantation and the impact of their dysregulation in recurrent implantation failure have yet to be characterized. Expert commentary : The proteomic investigation of the MMPs and their molecular pathways may enable scientists and clinicians to correct this dysregulation (via appropriate means of prevention and treatment), better manage embryo transfer during IVF cycles, and thus increase the ongoing pregnancy rate.